A Bibliometric Analysis of Nano Metal-Organic Frameworks Synthesis Research in Medical Science Using VOSviewer - Andika Purnama Shidiq (ASEAN Journal of Science and Engineering, 2023)
Nano MOFs (nMOFs) have now evolved as a new class of MOF with exciting applications. The purpose of this research is to perform bibliometric analysis on nMOFs for medical science by combining mapping analysis using VOSviewer software. Application reference manager used to obtain research data. The data obtained is the result of a search based on the keyword "nano metal-organic framework and madical science". From the search results, 1000 relevant published articles were found in the range of 2017-2021. The results showed that research on nano metal-organic frameworks and medical science has increased in 2017-2020, but it decreases since 2021. The main reason for the increase is the need for human health which continues to increase along with the emergence of new diseases. Although the increase should continue to occur every year, the decline in 2021 is due to social restrictions due to the COVID-19 pandemic, thus limiting the work space in the field of research. This study shows the importance of bibliometric analysis in providing analytical data about what phenomena occur. This research is expected to help and become a reference for researchers in conducting and determining the research theme to be taken.